2015
DOI: 10.4236/jcc.2015.33016
|View full text |Cite
|
Sign up to set email alerts
|

Design of Quasi-Optical Lens Antenna for W-Band Short Range Passive Millimeter-Wave Imaging

Abstract: A quasi-optical dielectric lens used for W-band focal plane array passive imaging has been developed. The imaging system requires the lens to form beam spot with 3 dB width less than 35 mm at distance of 3500 mm. The powerful optical design software ZEMAX was utilized to design the contours of the lens, and numerical method based on ray tracing and Huygens' Principle was processed to verify the design result. Measurement result shows that the 3 dB width of the beam spot formed by the lens is 34 mm at distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…These systems are structures that obtain images by collecting electromagnetic waves emitted from objects using sensitive radiometric receivers. These systems are passive as they use natural electromagnetic waves emitted from objects [2,3]. Although the image quality is relatively low compared to other systems (backscatter X-ray and active millimeter wave), the main advantage of PMMWIs is that they do not cause any harm to human health since they are not broadcast.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are structures that obtain images by collecting electromagnetic waves emitted from objects using sensitive radiometric receivers. These systems are passive as they use natural electromagnetic waves emitted from objects [2,3]. Although the image quality is relatively low compared to other systems (backscatter X-ray and active millimeter wave), the main advantage of PMMWIs is that they do not cause any harm to human health since they are not broadcast.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2015) developed a 43-cm diameter HDPE aspherical transition system at 89 GHz that was capable of imaging objects at a distance of 3.5 m with a resolution of 28 mm. Chen et al reported a similar system with 35 mm resolution at a distance of 3.5 m [2,20]. In 2011, an HDPE transition system was developed with a diameter of 50 cm at 94 GHz using a one-dimensional array of receivers [21].…”
Section: -Introductionmentioning
confidence: 99%
“…Since quasi-optical imaging systems should reduce the blurring effect in order to have an acceptable sharpness, an aspherical lens can be used [6]. A 43-cm diameter HDPE aspherical transition system at 89 GHz was capable of imaging the object at a distance of 3.5 m with a resolution of 28 mm developed by Zhou et al (2015) and Chen et al reported a similar system with 35 mm resolution at a distance of 3.5 m [1,18]. The development of HDPE transition system with a diameter of 50 cm at 94 GHz using one-dimensional array of receivers has also been reported in 2011 [19].…”
mentioning
confidence: 99%